Insights into the role of the conserved GTPase domain residues T62 and S277 in yeast Dnm1 - Banerjee, Riddhi; Mukherjee, Agradeep; Adhikary, Ankita; Sharma, Shikha; Hussain, Md Saddam; Ali, Md Ehesan; Nagotu, Shirisha (International journal of biological macromolecules, 2023)
Mitochondrial division is a highly regulated process. The master regulator of this process is the multi-domain, conserved protein called Dnm1 in yeast. In this study, we systematically analyzed two residues, T62 and S277, reported to be putatively phosphorylated in the GTPase domain of the protein. These residues lie in the G2 and G5 motifs of the GTPase domain. Both residues are important for the function of the protein, as evident from in vivo and in vitro analysis of the non-phosphorylatable and phosphomimetic variants. Dnm1T62A/D and Dnm1S277A/D showed differences with respect to the protein localization and puncta dynamics in vivo, albeit both were non-functional as assessed by mitochondrial morphology and GTPase activity. Overall, the secondary structure of the protein variants was unaltered, but local conformational changes were observed. Interestingly, both Dnm1T62A/D and Dnm1S277A/D exhibited dominant-negative behavior when expressed in cells containing endogenous Dnm1. To our knowledge, we report for the first time a single residue (S277) change that does not alter the localization of Dnm1 but makes it non-functional in a dominant-negative manner. Intriguingly, the two residues analyzed in this study are present in the same domain but exhibit variable effects when mutated to alanine or aspartic acid.